The Influence of Monopoly Media on The Students’ Interest in Learning Process of Elementary School - Nailil Muna Asshalikha; Ngabiyanto; Ellianawati; Bambang Subali; Nuni Widiarti (AR-RIAYAH: Jurnal Pendidikan Dasar, 2025)
Teachers, as facilitators, are required to create learning activities that involve active student participation, which encourages the development of a learning interest. The lack of media use in learning activities causes low student interest in learning. Monopoly media is one of the learning media that can attract students' attention to actively engage in the learning process his study examines the influence of monopoly media in increasing the learning interest of elementary school students using the Systematic Literature Review method through the Publish and Perish and Google Scholar platforms.  This study uses 19 recent research articles, which were selected based on predetermined inclusion and exclusion criteria. The analysis method used is qualitative descriptive. The research results show that the monopoly media is effective in increasing the learning interest of elementary school students.  Monopoly can stimulate students to participate actively, the interactive appearance of monopoly, and attracts students' interest in the learning process. Monopoly media is expected to be developed by using models, methods, or other approaches adapted to the learning needs of students.